Improvement of resistance against hydrogen embrittlement by controlling carbon segregation at prior austenite grain boundary in 3Mn-0.2C martensitic steels. (February 2023) - Okada, Kazuho; Shibata, Akinobu; Sasaki, Taisuke; Matsumiya, Hisashi; Hono, Kazuhiro; Tsuji, Nobuhiro
Abstract: This study challenged to improve the resistance against hydrogen embrittlement by increasing the concentration of carbon segregated at prior austenite grain boundary (PAGB), XPAGB, in low-carbon martensitic steels. The specimens with/without carbon segregation treatment (Non-seg and Seg specimens, respectively) had almost the same microstructure, other than higher XPAGB in the Seg specimen. While the uncharged Non-seg and Seg specimens exhibited similar mechanical properties, the maximum stress of the hydrogen-charged specimen was much higher in the Seg specimen than that in the Non-seg specimen even when diffusible hydrogen contents were almost the same. In addition, the fraction of intergranular fracture surface was much smaller in the Seg specimen. Based on these results, we conclude that the segregated carbon suppressed the accumulation of hydrogen around PAGB by site competition and increased cohesive energy of PAGB, leading to the significantly improved resistance against hydrogen-related intergranular fracture. Graphical abstract: Image, graphical abstract